Altered SPMs and age‐associated decrease in brain DHA in APOE4 female mice. Issue 9 (29th July 2019) - Martinsen, Anneloes; Tejera, Noemi; Vauzour, David; Harden, Glenn; Dick, James; Shinde, Sujata; Barden, Anne; Mori, Trevor A.; Minihane, Anne Marie
ABSTRACT: An apolipoprotein E ( APOE ) 4 genotype is the most important, common genetic determinant for Alzheimer disease (AD), and female APOE4 carriers present with an increased risk compared with males. The study quantified cortical and hippocampal fatty acid and phospholipid profiles along with select eicosapentaenoic acid (EPA)‐ and docosahexaenoic acid (DHA)‐derived specialized proresolving mediators (SPMs) in 2‐, 9‐, and 18‐mo‐old APOE3 and APOE4 male and female mice. A 10% lower cortical DHA was evident in APOE4 females at 18 mo compared with 2 mo, with no significant decrease in APOE3 or APOE4 males. This decrease was associated with a reduction in DHA‐phosphatidylethanolamine. Older APOE4 females had a 15% higher oleic acid content compared with young mice. Although no sex* APOE genotype interactions were observed for SPMs expressed as a ratio of their parent compound, higher cortical 18R/S‐hydroxy‐5Z, 8Z, 11Z, 14Z, 16 E ‐EPA, resolvin D3, protectin D1, 10S, 17S‐dihydroxy‐4Z, 7Z, 11 E, 13 E, 15Z, 19Z‐DHA (10S, 17S‐diHDHA), maresin 1, 17S‐hydroxy‐4Z, 7Z, 10Z, 13Z, 15 E, 19Z‐DHA, and 14S‐hydroxy‐4Z, 7Z, 10Z, 12E, 16Z, 19Z‐DHA were evident in females, and lower cortical 17 R ‐resolvin D1, 10S, 17S‐diHDHA, and 18‐HEPE in APOE4 . Our findings show a strong association between age, female sex, and an APOE4 genotype, with decreased cortical DHA and a number of SPMs, which together may contribute to the development of cognitive decline and AD pathology.—Martinsen, A., Tejera, N., Vauzour, D., Harden, G., Dick, J., Shinde, S., Barden, A., Mori, T. A., Minihane, A. M. Altered SPMs and age‐associated decrease in brain DHA in APOE4 female mice. FASEB J. 33, 10315–10326 (2019). www.fasebj.org